TINJAUAN MASLAHAH MURSALAH TENTANG TRADISI ONTALAN DALAM RESEPSI PERNIKAHAN (Studi Kasus di Desa Tunjung Kecamatan Ranguagung Kabupaten Lumajang) - Sodiq, Badrus; Abdillah, Achmad (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
The ontalan tradition is a hereditary tradition carried out by the people of Tunjung village. In this traditional procedure, it is to collect some money by throwing which is done by family, relatives and friends of the bridegroom. Many people in Tunjung Village who carry out this ontalan tradition do not understand the meaning, benefits, and laws of implementing this ontalan tradition. The formulation of the problem in this study is first how the practice of ontalan tradition in Tunjung village, second how to review the mursalah maslahah about ontalan tradition in wedding receptions in tunjung village. This thesis writing includes the type of field research (empirical juridical), with a case study approach, with interview, observation, and documentation data collection techniques. This research is a type of qualitative research (displaying research data word for word, descriptive analysis, interpretive or more dominant in the description of words). The data sources used are primary and secondary sources including photos, transcripts of interview guidelines, recordings, through purposive sumpling and time sumpling techniques. While the stages of data analysis are carried out by editing, classification, verification, conclusion, and analysis. The validity of the data applied is credibility, dependability, and confirmability. Based on these research methods, the results of research and discussion of the aspects of interviews and observations, researchers can understand that : (1). The implementation of the ontalan tradition in Tunjung Village is carried out in 2 ways, first carried out when the marriage proposal is directly and carried out when the proposal is only by the community, especially men in Tunjung Village. In this tradition there is a collection of some money by throwing and writing done by family, relatives, local community, and friends of the bridegroom. (2). The ontalan tradition in Tunjung Village contains positive values that can strengthen relationships / harmony between neighbors and other communities. The ontalan tradition in Tunjung Village is a form of tradition / custom that has been preserved by the ancestors and there is also a symbolic meaning in it. This ontalan tradition is also a necessity for all humans, because this tradition is a good purpose and in accordance with the purpose of shara'.